Recent Information on the Pathogenesis and Treatment of Hypoxic-Ischemic Brain Lesions in Newborns - G. A. Karkashadze; A. V. Anikin; E. P. Zimina; I. V. Davydova; Kh. M. Karimova; M. E. Zakharyan; L. S. Namazova-Baranova; O. I. Maslova; G. V. Yatsyk; S. I. Valieva; A. K. Gevorkyan (Union of pediatricians of Russia, 2016)
Hypoxic-ischemic brain lesions in children are the main environmental (non-genetic) factor in forming severe neurological pathology with subsequent disability. Scientists see the improvement of therapeutic approaches in acute phase of the disease as a main way to reduce the severity of neurologic complications. Due to the achievements in neuroscience in the field of perinatal hypoxicischemic injury mechanisms, three energy phases of pathologic events deployment were identified: primary (up to 6 hours from the lesion), secondary (6 to 24-48 h after the lesion) and distal tertiary (during few weeks, months). At the same time, necrosis, apoptosis, glutamate excitotoxicity, oxidative stress, inflammation, angiogenesis and neurogenesis make up separate links of destruction process. On the basis of new data on the pathogenesis of the disease, scientists from different countries have already offered modern treatment methods for perinatal hypoxic-ischemic injury with erythropoietin, allopurinol, melatonin, N-acetylcysteine, magnesium sulphate, albumin, -interferon, as well as with the help of controlled hypothermia, xenon, the use of stem cells, etc. This article presents a review of new data on pathogenesis and promising treatment methods for perinatal hypoxic-ischemic injuries.